Issues to Be Addressed and Hopefully Resolved in the Carotid Revascularization Endarterectomy Versus Stenting Trial 2. (May 2016) - Moore, Wesley S.
The superiority of carotid endarterectomy (CEA) plus best medical treatment (BMT) over BMT alone for the management of patients with asymptomatic carotid stenosis is based on randomized controlled trials that recruited patients up to 30 years ago. Best medical treatment has improved considerably since that time with respect to stroke prevention. Furthermore, a new carotid intervention has emerged during the last 2 decades and has gradually become established, that is, carotid artery stenting (CAS). Consequently, the efficacy of current BMT alone needs to be compared not only with CEA plus BMT but also with CAS plus BMT to determine which strategy achieves the optimal stroke prevention rates. This article highlights the purpose of the Carotid Revascularization Endarterectomy versus Stenting Trial (CREST) 2 and discusses the issues that CREST-2 will hopefully provide answers to.